تأثير النزال في بعض المتغيرات الفسيولوجية للعبة الملاكمة بحث وصفي على لاعبي الملاكمة فئة المتقدمين لبطولة المنطقة الشمالية للملاكمة 2007 - 2008 - عبدالأحد، ثانر; مغديد، ديار; شفيق، مريوان (جامعة القادسية - كلية التربية الرياضية, 2009)
يهدف البحث إلى: \ التعرف على تأثير النزال في بعض المتغيرات الفسيولوجية. \ يفترض الباحثون \ أن هناك فروق ذات دلالة إحصائية للمتغيرات الفسيولوجية قبل وبعد النزال. \ أما عينة البحث فتمثلت من (20) ملاكما للأوزان (48- 51- 54- 57) كغم وموزعين بالتساوي لكل وزن (5) ملاكمين، وقد تم أخذ القياسات الفسيولوجية في الراحة قبل النزال وبعد النزال مباشرة. \ الاستنتاجات \ وجود فروق ذات دلالة معنوية في معدل ضربات القلب ومعدل التنفس والضغط الانقباضي قبل النزال وبعده. \ عدم وجود فروق ذات دلالة معنوية في الضغط الانبساطي قبل النزال وبعده. \ التوصيات \ •\ إجراء دراسات متشابهة على فعاليات رياضية مختلفة. \ •\ إجراء دراسات مشابهة على متغيرات فسيولوجية أخرى. \ •\ على المدربين متابعة لاعبيهم من خلال إجراء اختبارات وظيفية وبدنية لأجل معرفة قابلياتهم الوظيفية والبدنية. The effect of competition on some of physiological variables in boxing match «A descriptive study on boxing varsity players of northern boxing championship» By: Dr. Thaeer Abdulahad, Dr. Deyar Maghdeed, Msc. Mariwan Shafeq \ Purpose of the study \ The purpose of this study was to identify the effect of competition on some of physiological variables. \ Hypothesis \ There was statistical differences in physiological variables of both competition, before and after. \ Methodology \ •\ A descriptive method was used in this study. \ •\ A sample of (20) boxers of weights (48- 51- 54- 57) Kg, were distributed of each weight (5) boxers. \ •\ The physiological tests were taken during rest and after competition too. \ Results and Recommendations \ 1.\ There were significant differences of heart beat and respiratory pressures ratio, before and after competition. \ 2.\ There was no significant differences on the diastolic pressure before and after competition. \ 3.\ More emphasis on physiological tests for boxers should be taken in to consideration from time to time. \ 4.\ More studies on physiological tests for boxers should be taken in to consideration. \ 5.\ Similar studies on different boxing weights should be taken in to consideration.
Keywords: ضغط الدم -- لعبة الملاكمة -- لاعبو الملاكمة -- بطولة المنطقة الشمالية للملاكمة -- ضربات القلب -- التنفس -- العراق -- اللياقة البدنية